2017
DOI: 10.1016/j.neo.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Withaferin A Inhibits Prostate Carcinogenesis in a PTEN-deficient Mouse Model of Prostate Cancer

Abstract: We recently demonstrated that AKT activation plays a role in prostate cancer progression and inhibits the pro-apoptotic function of FOXO3a and Par-4. AKT inhibition and Par-4 induction suppressed prostate cancer progression in preclinical models. Here, we investigate the chemopreventive effect of the phytonutrient Withaferin A (WA) on AKT-driven prostate tumorigenesis in a Pten conditional knockout (Pten-KO) mouse model of prostate cancer. Oral WA treatment was carried out at two different doses (3 and 5 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Oral administration of WFA with a dose of 3–5 mg/kg inhibited the activation of Akt and facilitated the FOXO3a-(Forkhead box O3a) mediated activation of Par-4 (prostate apoptosis response-4) leading to delayed tumor progression in preclinical prostate cancer models. Thus, WFA has been effective in up-regulating Par-4 and FOXO3a proteins (PI3K/Akt pathway regulated) in Pten -KO mice with a promising outcome for patients with Akt-activating mutations [83,84].…”
Section: Role Of Ws and Wfa In Various Cancersmentioning
confidence: 99%
“…Oral administration of WFA with a dose of 3–5 mg/kg inhibited the activation of Akt and facilitated the FOXO3a-(Forkhead box O3a) mediated activation of Par-4 (prostate apoptosis response-4) leading to delayed tumor progression in preclinical prostate cancer models. Thus, WFA has been effective in up-regulating Par-4 and FOXO3a proteins (PI3K/Akt pathway regulated) in Pten -KO mice with a promising outcome for patients with Akt-activating mutations [83,84].…”
Section: Role Of Ws and Wfa In Various Cancersmentioning
confidence: 99%
“…We reported recently that WA treatment suppresses fatty acid metabolism in LNCaP and 22Rv1 cells in vitro and neoplastic cells of the prostate in vivo in Hi‐Myc transgenic mice 20 . Collectively, these studies demonstrate therapeutic as well as chemopreventative potential of WA with no toxicity to normal cells in vitro or in vivo 16‐18 . These studies suggest that it may be worthwhile to investigate the mechanisms underlying anticancer effect of WA.…”
Section: Introductionmentioning
confidence: 64%
“…Inhibition of prostate cancer cell viability in the presence of WA is also associated with cell cycle arrest 15 . Two studies showed chemoprevention of prostate cancer development in TRansgenic Adenocarcinoma of Mouse Prostate (TRAMP) and PTEN‐deleted transgenic mouse models 16,17 . One of the desired characteristics of potential chemopreventive interventions is cancer cell‐selective mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, however, it is important to point out that withaferin A has been shown to inhibit growth of xenografted human prostate cancer cells in immune compromised mice as well as prevent prostate cancer development in transgenic mouse models. 33 , 34 , 35 …”
Section: Discussionmentioning
confidence: 99%